Schedule of investor’s procedure at build wind power plant on example Poland - Dolega, W. (Видавництво Національного університету “Львівська політехніка”, 2004)
This paper describes a schedule of investor’s procedure at build wind power plant. This schedule was elaborated on base of analysis of wind, technical, economical and legal conditions in Poland and composed of four phases: initial, stage of detailed data collecting, economical and stage of investment realisation.
Keywords: 621